Synthesis and Characterization of Vanadium Doped Hexagonal Rubidium Tungsten Bronze (Dhaka University Journal of Science, 2024)
Attempts have been made to synthesize vanadium doped rubidium hexagonal tungsten bronzes with the nominal composition RbxVyW1-yO3 (x = 0.30, 0.25, and 0.0 ≤ y ≤ x). The samples were synthesized using the solid state synthesis method in a silica glass tube under vacuum at (10-2 Torr) 700°C. The X-ray diffraction measurements reveal that a pure hexagonal tungsten bronze (HTB) phase can be formed with a 60% replacement of W5+ by V5+. The systematic incorporation of vanadium into the HTB lattice, as well as the reduction of V/W-O bond lengths in the xy plane and the lengthening of these bonds in the crystallographic c direction, are also revealed by Rietveld structure refinement of XRD data. The XRD results are supported by FTIR absorption spectra of the oxidized phases. Furthermore, an absorption signature develops as a function of y and exhibits a considerable increase in intensity with the eventual replacement of W5+ by V5+, showing a large decrease in the metallic like contribution and revealing the compounds' nonmetallic nature. Elemental analysis indicates good agreement with nominal values, demonstrating that vanadium was systematically incorporated into the RbxVyW1-yO3 system.Dhaka Univ. J. Sci. 72(1): 77-84, 2024 (January)